Integrated multi-omics profiling for risk stratification in Asians with COPD. - Meldrum,OW; Tiew,PY; Xu,H; Low,DY; Ivan,FX; Narayana,JK; Jaggi,TK; Ching,J; Chotirmall,SH (Respir Res, 2025)
BACKGROUND: Comorbidity-based risk stratification in Chronic Obstructive Pulmonary Disease (COPD) incompletely captures inherent biological heterogeneity, particularly in Asian populations that demonstrate high-risk clinical phenotypes including prior pulmonary tuberculosis. We investigated whether integrated sputum multi-omics could improve risk stratification in an Asian COPD cohort. METHODS: We conducted a prospective, multicenter assessment of N = 56 Asians with established COPD, classified as high- (N = 25; cardiovascular or ex-tuberculosis) or low-risk (N = 31; diabetic or low-comorbidity) based on established co-morbidity phenotyping. Sputum was subjected to mucus analysis (MUC5AC, MUC5B, mucus solids, rheology), metabo-lipidomics (LC-MS/MS) and microbiome assessment (shotgun metagenomics). Multivariate statistics was employed to integrate datasets. RESULTS: High-risk Asian COPD demonstrates abnormal mucus biochemistry characterized by elevated MUC5AC; extensive metabo-lipidomic alterations characterized by dysregulated tryptophan-kynurenine metabolism and lipid remodeling with enrichment of lysophosphatidylcholines and triacylglycerols. Microbial networks are disrupted in high-risk patients, typified by antagonistic interactions driven by K. pneumoniae, H. influenzae and Neisseria spp. Integrative assessment combining all datasets partitioned the cohort into two clusters: SNF 1 (N = 34) and SNF 2 (N = 22), the former representing an unfavorable group characterized by exacerbations, hospitalizations, mucus dysfunction, microbial pathogens and dysregulated metabo-lipidomic pathways. Remarkably, 42% (N = 13 of 31) of the originally classified low risk COPD exhibited the unfavorable SNF 1 endotype, distinguished by more severe exacerbations (hospitalizations), K. pneumoniae and elevated hypoxanthine, creatine, spermine and phosphatidylcholines. CONCLUSION: Integrative multi-omics